Efektivitas BUMdes pasca Pandemi Covid-19 Studi lapangan di BUMDes Gema Agung, Kecamatan Arma Jaya, Kabupaten Bengkulu Utara - Indah, Yuni; Rohati, Nely (Abiwara : Jurnal Vokasi Administrasi Bisnis, 2024)
On May 20, 2021, Sumber Agung Village was designated as a red zone. Based on data from the provincial COVID Handling Task Force, 11 people tested positive for COVID-19. The pandemic situation has greatly affected the business units formed by BUMDes Gema Agung. Several business units could not run according to expectations due to a decline in people's purchasing power. Meanwhile, BUMDes is expected to become a pillar of development and improvement of the village community's economy. In 2022, the government will establish a new normal era. February 2023: The government revokes the pandemic status. With this situation, researchers are interested in examining the effectiveness of BUMDes Gema Agung after the Covid-19 pandemic. This study aimed to get an overview of the efficacy of BUMDes after the COVID-19 pandemic. The method used is explorative qualitative. The data collection technique is a dept interview. The research instrument used was an interview guide. Research informants are the managers of BUMDes Gema Agung and village officials. The study results show that the effectiveness of BUMDes Gema Agung decreased after the COVID-19 pandemic. All managed business units experienced a decline in productivity. BUMdes Gema Agung cannot carry out economic activities as expected by the role of BUMdes to improve the economic welfare of village communities. From the results of this study, there should be a publlic policy t to revitalize BUMDes Gema Agung so that BUMDes are not stalled.